2004
DOI: 10.1023/b:bile.0000021957.37426.9b
|View full text |Cite
|
Sign up to set email alerts
|

Selective antimicrobial activity of chitosan on beer spoilage bacteria and brewing yeasts

Abstract: Chitosan (0.1 g l(-1)), assayed in a simple medium, reduced the viability of four lactic acid bacteria isolated during the beer production process by 5 logarithmic cycles, whereas activity against seven commercial brewing yeasts required up to 1 g chitosan l(-1). Antimicrobial activity was inversely affected by the pH of the assay medium. In brewery wort, chitosan (0.1 g l(-1)) selectively inhibited bacterial growth without altering yeast viability or fermenting performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…As can be observed, the three formulations assayed produced similar 100% inhibition hales (9.0±1.0 mm) and significant differences (p<0.05) with respect to the controls (6.5±0.5 mm). Films without drug also showed an inhibition zone (6.0±0.5 mm) that could be explained by the previously reported antimicrobial activity of CH (52)(53)(54)(55)(56)(57)(58)(59), which generates a matrix with antifungal properties. Surprisingly, the halo zone of the commercial cream (CC) containing an amount of ENC equal to that in the films was half in diameter for the both yeast assayed.…”
Section: Dissolution Assaysupporting
confidence: 53%
“…As can be observed, the three formulations assayed produced similar 100% inhibition hales (9.0±1.0 mm) and significant differences (p<0.05) with respect to the controls (6.5±0.5 mm). Films without drug also showed an inhibition zone (6.0±0.5 mm) that could be explained by the previously reported antimicrobial activity of CH (52)(53)(54)(55)(56)(57)(58)(59), which generates a matrix with antifungal properties. Surprisingly, the halo zone of the commercial cream (CC) containing an amount of ENC equal to that in the films was half in diameter for the both yeast assayed.…”
Section: Dissolution Assaysupporting
confidence: 53%
“…Antimicrobial activity of chitosan on beer spoilage bacteria and brewing yeasts was studied by Gil et al [174]. In this study antimicrobial activity of chitosan against four strains of LAB L. plantarum (Lp1,2,3), and Pediococcus sp.…”
Section: Chitosanmentioning
confidence: 97%
“…In vitro susceptibility assays in peptone water demonstrated that 0.1 g/L completely inhibited the Pediococcus sp. and Lp2 but 1 g/L chitosan was required to inhibit Lp1 and Lp3 strains [174]. To test the applicability of chitosan to control contamination in the brewing process yeast strain L1 (0.5 Â 10 7 CFU/mL) and Pediococcus sp.…”
Section: Chitosanmentioning
confidence: 99%
“…However, most industrial-scale S. cerevisiae strains cannot grow or ferment at temperature higher than 35°C (Limtong et al, 2007;Watanabe et al, 2010). Moreover, other methods have also been attempted to control Lactobacillus contamination, such as subjoining sulfite and hydrogen peroxide (Chang et al, 1997), adding peptides derived from bovine lactoferrin (Enrique et al, 2009), chitosan (Gil et al, 2004), and sulfuric acid (Pant and Adholeya, 2007;Tang et al, 2010). Sulfuric acid would cause high levels of sulfate ions in the wastewater and heighten the osmotic stress and change pH value of fermentation broth (Narendranath and Power, 2005).…”
Section: Introductionmentioning
confidence: 99%